Growing in public relations: lessons from the past - Abdul Razak al-Aidrus, Mohamed Ajmal (IIUM Press, International Islamic University Malaysia, 2009)
Growing In Public Relations—Lessons from the Past is a book specially written for young PR practitioners and all Communication and Public Relations students.